Trend in CT utilisation and its impact on length of stay, readmission and hospital mortality in Western Australia tertiary hospitals: an analysis of linked administrative data 2003–2015 - Rachael Moorin; Max K Bulsara; Jenny Doust; David Youens; Donald Mcrobbie; John Slavotinek; Thi Ninh Ha; Cameron Wright; Sviatlana Kamarova (BMJ Open)
Objective High use of CT scanning has raised concern due to the potential ionising radiation exposure. This study examined trends of CT during admission to tertiary hospitals and its associations with length of stay (LOS), readmission and mortality.Design Retrospective observational study from 2003 to 2015.Setting West Australian linked administrative records at individual level.Participants 2 375 787 episodes of tertiary hospital admission in adults aged 18+ years.Main outcome measures LOS, 30-day readmissions and mortality stratified by CT use status (any, multiple (CTs to multiple areas during episode), and repeat (repeated CT to the same area)).Methods Multivariable regression models were used to calculate adjusted rate of CT use status. The significance of changes since 2003 in the outcomes (LOS, 30-day readmission and mortality) was compared among patients with specific CT imaging status relative to those without.Results Between 2003 and 2015, while the rate of CT increased 3.4% annually, the rate of repeat CTs significantly decreased −1.8% annually and multiple CT showed no change. Compared with 2003 while LOS had a greater decrease in those with any CT, 30-day readmissions had a greater increase among those with any CT, while the probability of mortality remained unchanged between the any CT/no CT groups. A similar result was observed in patients with multiple and repeat CT scanning, except for a significant increase in mortality in the recent years in the repeat CT group.Conclusion The observed pattern of increase in CT utilisation is likely to be activity-based funding policy-driven based on the discordance between LOS and readmissions. Meanwhile, the repeat CT reduction aligns with a more selective strategy of use based on clinical severity. Future research should incorporate in-hospital and out-of-hospital CT to better understand overall CT trends and potential shifts between settings over time.